Relevansi Akuntansi CSR dalam Mendukung Keberlanjutan Bisnis: Studi pada UMKM di Kota Makassar - Tenriwaru; Syamsu Alam; Andi Nurwanah (Jurnal Buana Akuntansi, 2026)
This study aims to examine the relevance of Corporate Social Responsibility (CSR) accounting in supporting business sustainability. The research problem arises from the limited understanding of companies regarding the role of CSR accounting, which is often perceived merely as a reporting tool rather than a mechanism for social accountability and sustainability strategy. This study adopts a qualitative approach using a case study method on several companies operating in Makassar City. Data were collected through in-depth interviews with management, analysis of CSR reporting documents, and observation of CSR program implementation. The findings reveal that CSR accounting plays a significant role in supporting business sustainability by enhancing transparency, strengthening corporate legitimacy, and fostering long-term relationships with stakeholders. Nevertheless, the implementation of CSR accounting still faces challenges, including the lack of standardized operational guidelines and the limited integration of CSR into corporate accounting systems. The implications of this study highlight the importance of strengthening systematic and context-based CSR accounting practices to enhance their contribution to sustainable business, particularly for companies in Eastern Indonesia. Keywords: CSR accounting, business sustainability, social accounting, corporate social responsibility